Judar och judendom i kristen skolundervisning - Illman, Karl-Johan (Nordisk judaistik, 1986)
International research projects on the picture of Jews and Judaism presented in Christian textbooks and curricula have been carried out for some 25 years. The pioneer work is B.E. Olson’s Faith and Prejudice: Intergroup Problems in Protestant Curricula (1963) undertaken at Yale University. Olson focused not only on the question of how Jews are viewed, but also how Catholics and Protestant groups were pictured in the same materials. Moving on the European scene, we have research projects in the 60s carried out on Catholic textbooks in French language from France, Belgium, Switzerland and Canada.